Contribuição ao conhecimento dos Metopiinae (Hymenoptera, Ichneumonidae) do Brasil, com ênfase em ambientes de mata e cerrado da Bacia Hidrográfica do Rio Mogi-Guaçu - Araújo, Carolina Rodrigues de (2011)
ABSTRACT This study aimed to contribute to the knowledge of the Brazilian fauna of Metopiinae through the characterization and quantification of their genus and species in areas of semideciduous forest and savanna in Mogi-Guaçu River Basin, located in Minas Gerais and São Paulo. Malaise traps were installed in 10 sampling points located in six localities along the entire basin, during August 2009 to September 2010. It was collected 195 specimens of Metopiinae, distributed in 41 taxa (34 species- with seven new species-, and seven "close species") among then we found 15 new records for the Brazilian fauna (14 species and one genus). The species Exochus izbus Gauld & Sithole, 2002 and Exochus sp. n. 1 were more abundant and had better distribution, being found in five and six fragments, respectively. The sampling points relating to the localities of Andradas-MG and Luiz Antônio-SP had higher abundance and greater species richness of Metopiinae. The sampling points relating to Bom Repouso-MG (sampling point II: Boa Vereda de Cima) and Jacutinga-MG (Morro da Forquilha) had considerable richness of species and highest values of diversity and evenness. The sampling points of Luiz Antônio-SP, analyzed separately due to sampling differences, also had high diversity index and evenness, and the area of riparian forest had the highest richness and abundance of Metopiinae. The fragments with more faunistic similarity were sampling point I (Serra dos Garcias) and III (Damásio district), both in Bom Repouso-MG, with 70% of similarity. It was found that Metopiinae are more abundantly collected in the rainy season, confirming the relationship between abundance and seasonality. Descriptions of new species, the characterization of other species and more information about geographical distribution of Metopiinae were other important contributions of this work.